Transformational Leadership and Affective Commitment in the Public Sector: The Role of Public Service Motivation as a Mediator - Hanafi, Ismed; Kurnianto Tjahjono, Heru; Rahayu DA, Meika Kurnia Puji (SBM ITB, 2022)
Abstract. Public service motivation (PSM) has become a popular topic discussed in various studies concerning the public sector. However, there is still limited literature discussing PSM, transformational leadership, and affective commitment simultaneously. Therefore, this study aims to examine the role of transformational leadership on affective commitment in the public sector by considering PSM as a mediating variable in the Indonesian context. This study applies a quantitative approach based on data collected from 172 Customs and Excise employee respondents. Primary data was obtained through a purposive sampling method and analyzed using a structural equation model (SEM). The results indicate a positive and significant influence of transformational leadership on PSM, PSM on affective commitment, and transformational leadership on affective commitment. However, the findings show that PSM does not mediate the effect of transformational leadership on affective commitment. The study also addresses some theoretical contributions and managerial implications concerning these topics.Keywords: Transformational leadership, affective commitment, public sector, public service motivation, mediating variableAbstrak. Motivasi Pelayanan Publik (MPP) telah menjadi topik popular yang dibahas di berbagai penelitian tentang sektor publik. Namun demikian, literatur yang mendiskusikan MPP dengan kepemimpinan transformasional dan komitmen afektif secara bersamaan masih terbatas. Oleh karenanya, studi ini bertujuan untuk menguji peran kepemimpinan transformasional terhadap komitmen afektif di sektor publik dengan mempertimbangkan MPP sebagai variabel pemediasi dengan konteks Indonesia. Studi ini menggunakan pendekatan kuantitatif berdasarkan data yang didapat dari 172 responden Bea dan Cukai. Data primer diperoleh melalui purposive sampling method dan selanjutnya diolah dengan menggunakan Structural Equation Model (SEM). Hasil penelitian menunjukkan bahwa terdapat pengaruh positif dan signifikan antara kepemimpinan transformasional terhadap MPP, MPP terhadap komitemen afektif dan kepemimpinan transformasional terhadap komitmen afektif. Namun demikian, MPP terbukti tidak memediasi pengaruh kepemimpinan transformasional terhadap komitmen afektif. Kontribusi secara teoritis dan implikasi manajerial juga disajikan dalam penelitian ini.Kata kunci: Kepemimpinan transformasional, komitmen afektif, sektor publik, motivasi pelayanan publik, variable pemediasi